THE ROLE OF HOSPITALITY TO IMPROVE THE PATIENT EXPERIENCE IN HOSPITAL : A SCOPING REVIEW - Monica Vidian; Wahyu Sulistiadi (Fakultas Kesehatan Universitas Muhammadiyah Sumatera Barat, 2024)
The hospitality industry has a strong focus on providing excellent customer service and creating positive experiences for guests. These same principles can be applied to the healthcare industry to improve the patient experience in hospitals. When patients are in the hospital, they may experience vulnerability, anxiety, and uncertainty about their health and treatment. Thus, providing a welcoming and comfortable environment can create a more positive and supportive environment for patients which may help ease their stress and improve their overall experience and contribute to better health outcomes.